Hepatitis A and E seropositivity and nucleic acid detection among chemical bombardment survivors in Iraqi Kurdistan Region - Hama, Salih Ahmed; Ahmed, Shawnm (Sulaimani Journal for Pure and Applied Sciences, 2017)
The current study was carried out to determine the percentage rates of anti-hepatitis A and E (HAV and HEV) IgG and IgM seropositivity and RNA among chemical bombarded survivors in different regions in Iraqi Kurdistan. Blood samples were collected randomly from 92 chemical bombed exposures and 45 non-exposures -controls- from July to November 2013. ELISA and conventional, nested PCR techniques were followed to detect anti-hepatitis A and E IgG, IgM and RNA respectively. Lymphocyte counting also was done for all tested exposures and controls. It was observed that the percentage rates of hepatitis A seropositivity were higher than hepatitis E. All tested exposures (100%) were seropositive for anti- HAV IgG, whereas 61.79% were positive for anti-HEV IgG. Similarly, anti-HAV IgM seropositivity was higher (8.9%) than that of anti- HEV (1.089%). Current results revealed that there were significant differences between exposures and controls regarding anti-HAV and anti-HEV IgG (p= 0.0001 and 0.0002), whereas no significant differences were observed between the two tested groups concerning anti-HAV and anti-HEV IgM seropositivity (p= 0.621 and 0.56). Moreover, significant differences were found among anti-HAV IgG and IgM as well as anti-HEV IgG and IgM seropositivity among exposures themselves (p= 0.000 and 0.0055) respectively. The percentage rate of hepatitis A RNA positivity was 15.68%, whereas no positive results were seen for HEV. Geographical distribution of exposures was appeared to be significantly effective on all obtained results (seropositivity and RNA detection) (p ‹ 0.05). It was noticed that lymphocytes were significantly different between HAV- seropositive and seronegative exposures (p ‹ 0.05). A high percentage rate of exposures with positive results for anti-HAV, anti-HEV, and PCR positive results, were suffering from lymphopenia. The highest lymphocyte abnormalities were among exposures with anti-HAV IgM followed by anti-HAV IgG then anti-HEV IgG seropositive exposures.
Keywords: Hepatitis A virus; Hepatitis E virus; Chemical warfare; Halabja